Preparation and Characterization of Celecoxib Agglomerated Nanocrystals and Dry Powder Inhalation Formulations to Improve its Aerosolization Performance - Sepideh Mardani 1, Maryam Maghsoodi 2 * , Saeed Ghanbarzadeh 3,4, Ali Nokhodchi 5, Shadi Yaqoubi 6, Hamed Hamishehkar 7 * (Tabriz University of Medical Sciences, 2017)
Background: Celecoxib is a non-steroidal anti-inflammatory drug used extensively in the treatment of pain, arthritis, and cancers. However, its administration is limited due to its several disadvantages including gastric irritation and hepatic first pass metabolism. Among numerous methods for pulmonary drug delivery, dry powder inhalation systems show the promising approach to be used as alternative routes for oral drug delivery. This study was conducted to develop agglomerated nanocrystals and carrier-free Celecoxib dry powder inhalation formulation for pulmonary delivery in lung cancer treatment. Methods: Spray dried Celecoxib, Celecoxib nanocrystals, and agglomerated nanocrystals were characterized in the case of particle size distribution, crystallinity, and aerosolization efficiency including mass median aerodynamic diameter (MMAD), fine particle fraction (FPF), and geometric standard deviation (GSD) by Next Generation Impactor (NGI). Results: Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analyses showed the lack of any interaction and polymorphism in the prepared formulations. Results showed that the optimized spray-dried formulation of Celecoxib was in the appropriate size range, and shape for pulmonary delivery. MMAD, FPF, and GSD values for spray-dried formulation were 31.93±3.93%, 4.82±0.21 µm, and 1.81±0.05, respectively. Conclusion: Although the agglomerated nanocrystals of Celecoxib showed comparable aerosolization efficiency indexes with carrier free spray-dried Celecoxib formulation, further investigations are necessary to optimize the agglomeration process to obtain agglomerated nanocrystals of Celecoxib with improved aerosolization efficiency indexes.